Motor clinical progression in a series of pediatric Duchenne and Becker muscular dystrophy cases - Zakiah Nur Istianah; Sunartini Sunartini; Sasmito Nugroho (Paediatrica Indonesiana, 2019)
Muscular dystrophy is a neuromuscular disorder that begins with muscle weakness and impaired motor function. Duchenne muscular dystrophy (DMD) is more severe and destructive than Becker muscular dystrophy (BMD), and both are progressive in nature. These 2 types of muscular dystrophy are caused by mutations in related to X-chromosome genes.1 The mutations that occur in DMD are nonsense mutations. Deletion is present in 60% of DMD cases, while duplication occurs in 10% of DMD cases, resulting in loss of dystrophin protein. Mutations in BMD are missense mutations, so dystrophin is still formed, but in decreased amounts and quality.2,3 The prevalence of DMD was reported to be three times greater than that of BMD, with a prevalence of 1.02 per 10,000 male births vs. 0.36 per 10,000 male infants, respectiveley.4 Anatomical pathology examination revealed loss of dystrophin in the examination of muscle biopsy without the presence of evidence leading to other neuromuscular diseases. Clinical DMD symptoms begin to appear at the age of 2-4 years. The child is observed to fall often and has difficulty climbing stairs. Muscle weakness worsens, especially in the upper limbs, continuing with heart and respiratory problems. The main causes of death in DMD are respiratory failure and heart failure.5 The BMD has varied clinical symptoms, beginning with the appearance of myalgia, muscle cramps, and arm weakness progressing towards myopathy. Some patients are asymptomatic until the age of 15, but 50% of patients show symptoms at age 10, and almost all by age 20.6